2023
DOI: 10.3390/diagnostics13061133
|View full text |Cite
|
Sign up to set email alerts
|

Delaminated Tears of the Rotator Cuff: MRI Interpretation with Clinical Correlation

Abstract: (1) Background: A delaminated tear is described as a horizontal split in the tendon substance. This review summarizes the clinical and radiologic characteristics of delaminated tears of the rotator cuff. (2) Methods: Initial radiological characteristics of a delaminated tear include the horizontal component of a partial-thickness tear determined using magnetic resonance (MR) arthrography. As demonstrated using indirect MR arthrography, the tear gradually progresses to be defined as either horizontal intrasubst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 56 publications
1
1
0
Order By: Relevance
“… 5 , 18 This histological difference between the two layers reflects different biomechanical properties: superficial (bursal) layer is more resistant to tensile load because it elongates more than articular layer, which elongates poorly but torn more easily, and then is more vulnerable to a tensile load than the bursal layer. 4 , 5 A recent study based on a five-layered model of supraspinatus tendon insertion on greater tuberosity on MRI images showed that supraspinatus tendon delaminated tears usually occur between the second (densely packed parallel tendon fibers, consistent with bursal layer of supraspinatus tendon) and third (smaller fibers that cross over one another at 45° consistent with deep layer of supraspinatus tendon) layers, 11 in agreement with previous studies. According to this five-layered model, however, a second plane of cleavage exists at the level of the fourth layer, composed of loose connective tissue containing thick collagen bands running perpendicular to tendons fibers (called the “rotator cable” 3 , 10 ).…”
Section: Discussionsupporting
confidence: 85%
“… 5 , 18 This histological difference between the two layers reflects different biomechanical properties: superficial (bursal) layer is more resistant to tensile load because it elongates more than articular layer, which elongates poorly but torn more easily, and then is more vulnerable to a tensile load than the bursal layer. 4 , 5 A recent study based on a five-layered model of supraspinatus tendon insertion on greater tuberosity on MRI images showed that supraspinatus tendon delaminated tears usually occur between the second (densely packed parallel tendon fibers, consistent with bursal layer of supraspinatus tendon) and third (smaller fibers that cross over one another at 45° consistent with deep layer of supraspinatus tendon) layers, 11 in agreement with previous studies. According to this five-layered model, however, a second plane of cleavage exists at the level of the fourth layer, composed of loose connective tissue containing thick collagen bands running perpendicular to tendons fibers (called the “rotator cable” 3 , 10 ).…”
Section: Discussionsupporting
confidence: 85%
“…Walz et al [5] defined a delaminated rotator cuff tear as a tear with horizontal retraction on the joint or bursa side, thickening of the tear edge, or a tear within the tendon. A delaminated rotator cuff tear is currently defined as a horizontal tear within the tendon that requires treatment and may be accompanied by partial intratendinous fiber retraction [3, 6, 7]. Subacromial impingement [8], rotator cuff degeneration [9], rotator cuff delamination characteristics, and histologic differences between the rotator cuff articular and bursal layers are risk factors of rotator cuff delamination tears.…”
Section: Introductionmentioning
confidence: 99%